2021
DOI: 10.21037/apm-21-105
|View full text |Cite
|
Sign up to set email alerts
|

Predictive efficacy of weaning index on mechanical ventilation evacuation

Abstract: Background: The timely weaning of mechanical ventilation can shorten intensive care unit (ICU) stay times and reduce the complications related to mechanical ventilation. This study sought to investigate the predictive role of a weaning index (WI) on mechanical ventilation evacuation by measuring minute ventilation volume (MVV) across different ventilation modes.Methods: Patients suffering from respiratory failure for a variety of reasons were included in the study if they received mechanical ventilation for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the largest multicenter study to date, by Frutos-Vivar et al [ 81 ], 121 (13.4%) of 900 patients who passed the SBT had extubation failure; they showed that a 1-unit increase in the RSBI increased the risk of extubation failure by 0.9%. However, the reference value of the RSBI has varied in different studies, and several studies have suggested values (57–80 breaths/min/L) much lower than the previously recommended value of 105 breaths/min/L [ 81 , 83 , 85 , 87 ]. In four studies evaluating the predictive power of the RSBI for extubation failure, the area under the receiver operating characteristic curve ranged from 0.63 to 0.92, indicating good to excellent predictive power [ 82 , 83 , 85 , 87 ].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In the largest multicenter study to date, by Frutos-Vivar et al [ 81 ], 121 (13.4%) of 900 patients who passed the SBT had extubation failure; they showed that a 1-unit increase in the RSBI increased the risk of extubation failure by 0.9%. However, the reference value of the RSBI has varied in different studies, and several studies have suggested values (57–80 breaths/min/L) much lower than the previously recommended value of 105 breaths/min/L [ 81 , 83 , 85 , 87 ]. In four studies evaluating the predictive power of the RSBI for extubation failure, the area under the receiver operating characteristic curve ranged from 0.63 to 0.92, indicating good to excellent predictive power [ 82 , 83 , 85 , 87 ].…”
Section: Resultsmentioning
confidence: 96%
“…However, the reference value of the RSBI has varied in different studies, and several studies have suggested values (57–80 breaths/min/L) much lower than the previously recommended value of 105 breaths/min/L [ 81 , 83 , 85 , 87 ]. In four studies evaluating the predictive power of the RSBI for extubation failure, the area under the receiver operating characteristic curve ranged from 0.63 to 0.92, indicating good to excellent predictive power [ 82 , 83 , 85 , 87 ]. Segal et al [ 84 ] compared the risk of extubation failure according to changes in the variation of RSBI values measured continuously for 2 hours and reported that an increase in the RSBI of 20% or more was associated with extubation risk.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation